Penerapan Sistem Informasi Manajemen Perizinan Terpadu (SIMPADU) Dalam Pelayanan Kapal di Pelabuhan Makassar - Enjelika Marbaroka; Satria Satria; Sarifuddin Sarifuddin (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The Port of Makassar demands ship service mechanisms that are rapid, effective, and transparent in order to support smooth port operations. This study focuses on analyzing the implementation of the Integrated Licensing Management Information System (SIMPADU) as an effort to improve the performance of vessel licensing services at the port. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct field observations, and analysis of relevant documents. The results indicate that the use of SIMPADU has significantly streamlined the vessel licensing process by shortening processing time, lowering administrative costs, increasing service transparency, and improving access to licensing information for stakeholders. These improvements contribute to reduced vessel waiting times and better coordination among related agencies operating within the port environment. However, several obstacles remain, including inadequate supporting infrastructure, unstable network connectivity, and limited human resource capabilities in operating the system optimally. Despite these challenges, SIMPADU plays an important role in supporting the modernization of port services and the digital transformation of licensing procedures. To maximize its benefits, continuous capacity building through training programs and stronger integration of cross-agency services are required to ensure sustainable and efficient port service delivery.